2003
DOI: 10.1002/ange.200351461
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Wafer‐Scale Production of ZnO Nanowire Arrays

Abstract: Since the first report of ultraviolet lasing from ZnO nanowires, [1] substantial effort has been devoted to the development of synthetic methodologies for one-dimensional ZnO nanostructures. Among the various techniques described in the literature, evaporation and condensation processes are favored for their simplicity and high-quality products, but these gas-phase approaches generally require economically prohibitive temperatures of 800-900 8C.[2] Despite recent MOCVD schemes that reduced the deposition temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
126
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(132 citation statements)
references
References 21 publications
6
126
0
Order By: Relevance
“…1,33,45 Thermal treatment is one of the most effective methods to remove these defects. In this work, annealing of ZnO nanorods at 350 1C for 1 hour in nitrogen and oxygen was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…1,33,45 Thermal treatment is one of the most effective methods to remove these defects. In this work, annealing of ZnO nanorods at 350 1C for 1 hour in nitrogen and oxygen was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among these 1D nanomaterials, many novel synthesis techniques have then been developed, including chemical vapor deposition (CVD), [8][9][10] hydrothermal methods, [11][12][13] and template-assisted electrodeposition, etc; [14][15][16] however, all of these fabrication schemes come with different process-related disadvantages. For example, CVD has been widely employed for the growth of 1D semiconductor nanostructures, [17,18] in which this technique is still far from being compatible with the large-scale manufacturing platform due to the rather high fabricating cost, rigorous process control, low production throughput, and complicated subsequent device fabrication scheme.…”
mentioning
confidence: 99%
“…On the other hand, it was reported that the anionic surfactant NaAOT can be made to form micelles with diverse shapes by adjusting experimental parameters. [33][34][35][36] The self-assembled AOT À layers at the interface of water and oil could act as template for growing ZnO Fast growth along h21 1 0i results in the formation of a hexagonal disk (Figure 5 a). Slight bending of the selfassembled AOT À monolayer makes it possible to accommodate local strain in the disk by formation of small-angle grain boundaries closely parallel to {21 1 0}.…”
mentioning
confidence: 99%